2020
DOI: 10.2478/asmj-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the correlation between impacted canine and malocclusions

Abstract: Introduction: Tooth impaction is defined as the absence of a tooth on the arch, after its normal eruption age. The main reason canines are impacted is the lack of space required for the tooth to erupt.Aim of study: The main objective of this study is to determine the types of malocclusions associated with canine impaction (Lindauer classification). A secondary objective is to establish the correlation between these parameters and identification of subjects with high risk of canine impaction based on pre-existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In a study conducted by Pop et al [7] to determine the types of malocclusion associated with impacted canines, they found that impacted canines were most commonly associated with Class II malocclusion and sector 4 according to Lindauer's sectoral classification, which is consistent with this present study. It is thought that the reason for this may be that as the relationship of the canine tooth with the lateral tooth increases, the possibility of becoming impacted increases.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In a study conducted by Pop et al [7] to determine the types of malocclusion associated with impacted canines, they found that impacted canines were most commonly associated with Class II malocclusion and sector 4 according to Lindauer's sectoral classification, which is consistent with this present study. It is thought that the reason for this may be that as the relationship of the canine tooth with the lateral tooth increases, the possibility of becoming impacted increases.…”
Section: Discussionsupporting
confidence: 91%
“…Panoramic and lateral cephalometric radiographs are usually taken from patients following orthodontic treatment and minimize radiation exposure. These radiographs provided sufficient data for the present study [ 7 ], and panoramic radiographs were used to evaluate impacted canines’ angular and linear position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…51 However, to manage the principal use of CBCT in dental subjects and specialties, it is important to analyze tooth location, length, direction, related structures, and dental arch measurements. 82 The radiation risk when utilizing CT is extremely questionable. As a result, the main advantage of CBCT versus a CT scan is the lower radiation exposure.…”
Section: Discussionmentioning
confidence: 99%